INTERELASI ISLAM DAN BUDAYA: STUDI TRADISI UPAH-UPAH DI ASAHAN, SUMATERA UTARA - Lubis, Ihza Nurfadli Ramadhan (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Upah-upah is a tradition that developed on the East coast of North Sumatra. This tradition functions as a tool to express oneself in celebrations in Malay society, especially in Asahan, North Sumatra. In essence, this tradition does not only originate from the coast which is actually Muslim but is also carried out by the mountainous communities of North Sumatra who are non-Islamic. The initial emergence of this tradition was the same as the traditions that developed in society in general, namely that it was not far from "mystical and magical" things. However, as time goes by, the Malay people's religious understanding of Islam continues to evolve, giving rise to the desire to change practices that deviate from Islamic teachings by discarding mystical parts and implementing parts that do not conflict with the Shari'a. The problems to be researched are the origins of the wage-upah tradition in Asahan, what is the process of implementing the Upah-upah tradition, what Islamic values are contained in the Upah-upah tradition. This research uses a descriptive-qualitative method which aims to describe and analyze Islamic activities and values in the Upah-upah tradition in Asahan. Researchers use a social anthropology approach as an auxiliary science. The results of the research found the fact that the Upah-upah tradition plays a role in filling diversity in the life of the Asahan Malay community and has Islamic values/elements without having to abandon its traditional (Malay) color. Thus, this research still needs further exploration to analyze the community's views on theUpah-upah tradition.Keywords: Islam, Malay, Upah-upah Tradition, and the Coast.